Evaluating capability of two halophyte plants for phytoextraction of cadmium from contaminated soils - Mahboubeh Mazhari; Safoora Asadi Kapourchal; Mehdi Homaee (All Life)
Selecting an appropriate plant is a key factor for the phytoextraction of heavy metals from contaminated soils. The possibility of using two halophytes for the remediation of cadmium (Cd) from contaminated soils was investigated. Consequently, an experiment with Chenopodium album L. and Chenopodium botrys L. including Cd treatments of 0, 5,10, 20, 40, 60, 80 and 100 ppm was conducted. Designated analyses including fresh weight, dry weight, and Cd concentrations in shoots and roots were performed. Results indicated that for both plants, a logarithmic model performed best to demonstrate the relationship between total soil Cd with shoot Cd and dry matter. Although both halophytes had considerable capability to remediate Cd from soils, C. botrys demonstrated greater potential to accumulate Cd in shoots. The range of bioconcentration factor (BCF) in C. botrys was obtained to be 0.8 to 8.8 and in C. album was 0.4 to 1.73. For C album, BCF in most treatments was lower than 1.0, but for C. botrys, it was mostly larger than 1.0. Although both plants can be used as hyperaccumulators to remediate Cd-polluted soils, the clean-up time of C. album under higher Cd concentrations was shorter than C. botrys L.